Goosebump horror land Creep from the deep - Stine, R.L (New York, Scholastic Inc., 2008)
Billy and Sheena go with their Uncle, Dr. Deep, to search for treasure and are pursued by pirates who have been dead for two hundred years, and when Billy and Sheena return to land and visit Horrorland they encounter their worst fears.
Keywords: English, Fiction